2013
DOI: 10.4103/1793-5482.121686
|View full text |Cite
|
Sign up to set email alerts
|

Success rate of endoscopic third ventriculostomy in infants below six months of age with congenital obstructive hydrocephalus (a preliminary study of eight cases)

Abstract: Aim:In this study, we were assessing the outcome of Endoscopic Third Ventriculostomy (ETV) in infants below six months of age in cases of congenital obstructive hydrocephalus.Materials and Methods:The study was done prospectively on eight cases of obstructive hydrocephalus in infants younger than six months of age to assess the success rate of ETV as a primary treatment for hydrocephalus in this age group; in cases of evident failure, a ventriculo-peritoneal (VP) shunt was applied.Results:Despite eliminating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 32 publications
(55 reference statements)
0
12
0
Order By: Relevance
“…Endoscopic techniques are increasingly being used in spine,[ 208 209 210 ] skull base[ 211 212 213 ] and intracranial pathologies. [ 214 215 216 ] Endoscopic technique can be used alone in TN[ 217 218 ] or as an adjuvant to microscope[ 219 220 221 ] It is a minimally invasive technique,[ 221 222 ] allows better visualization of entire root from pons to ganglion[ 217 222 223 ] including ventral aspect. [ 223 ] The endoscope is a valuable tool during MVD, especially when a bony ridge hiding the direct microscopic view of vascular conflict.…”
Section: Endoscopic Vascular Decompressionmentioning
confidence: 99%
“…Endoscopic techniques are increasingly being used in spine,[ 208 209 210 ] skull base[ 211 212 213 ] and intracranial pathologies. [ 214 215 216 ] Endoscopic technique can be used alone in TN[ 217 218 ] or as an adjuvant to microscope[ 219 220 221 ] It is a minimally invasive technique,[ 221 222 ] allows better visualization of entire root from pons to ganglion[ 217 222 223 ] including ventral aspect. [ 223 ] The endoscope is a valuable tool during MVD, especially when a bony ridge hiding the direct microscopic view of vascular conflict.…”
Section: Endoscopic Vascular Decompressionmentioning
confidence: 99%
“…Zohdi et al published a prospective series of 8 cases of infants below six months who underwent ETV as primary treatment of congenital obstructive hydrocephalus. ETV was efficient in one case only and the study was discontinued [16]. In the same way, Helseth et al in 2000 reported SR of 62% for patients above 6 months and only an 8% success for those younger than 6 months of age.…”
Section: Etv Success Rates In Children Less Than 2 Yearsmentioning
confidence: 79%
“…In spite of its numerous advantages in treating obstructive hydrocephalus, ETV is still not widely or routinely used in Sub-Saharan African countries like Cameroon. Besides the works of Benjamin C Warf in Uganda [5]- [7] [10], we found only five reports addressing this procedure in Africa: two in Nigeria [1] [3], one in Malawi by Kamalo P [2], one in Kenya and Tanzania by Piquer et al [4], one in South Africa [11], and one in Egypt [12]. This is really surprising because ETV is much more crucially advantageous in Africa where shunt related problems are very difficult to manage appropriately compared to developed countries.…”
Section: Sub-saharan Africa Contextmentioning
confidence: 99%
“…In Uganda in 2005, Warf BC [8] had reported success rates of 81% and 90% in children older than 1 year depending on etiology. [12]. Post-infectious, post-haemorrhagic and previously shunted hydrocephalies were also considered contra-indications for ETV.…”
Section: Success Rates Of Etvmentioning
confidence: 99%